164k views
4 votes
Help fill in the blanks on the second problem i have the answer already

Help fill in the blanks on the second problem i have the answer already-example-1
User Touch
by
4.6k points

1 Answer

6 votes

Given equation is,


g(x)=x^2+3x-10

Then,


\begin{gathered} g(f(x))=\lbrack f(x)\rbrack^2+3\lbrack f(x)\rbrack-10 \\ =(x+4)^2+3(x+4)-10 \\ =x^2+8x+16+3x+12-10 \\ =x^2+11x+18 \end{gathered}

So in the first blank, it will be,


=(x+4)^2+3(x+4)-10

And in the second blank it will be,


undefined

User David Mason
by
4.8k points